2009
DOI: 10.4314/scinat.v6i1.48578
|View full text |Cite
|
Sign up to set email alerts
|

Variations saisonnières des indices épidémiologiques de trois monogènes parasites de <i>Sarotherodon melanotheron</i> (pisces : Cichlidae) dans le lac d’ayamé i (Côte d’Ivoire)

Abstract: Résumé Abstract Seasonal variations of the epidemiological index of three Monogenean parasites of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
2
9
0
1
Order By: Relevance
“…For example, Bilong and Tombi (2005) showed that two Monogeneans namely Dactylogyrus in solitus and D. bopeleti gills parasites from Barbus martorelli reached their highest prevalence and their maximum intensity during the rainy seasons. Blahoua et al (2009) also observed that C. acerbus, C. halli and Scutogyrus minus appeared to be more prevalent and more abundant in long rainy season. Our results can be explained by water temperature which is assumed to be an important factor in controlling the occurrence of Monogeneans Simkova et al, 2001).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…For example, Bilong and Tombi (2005) showed that two Monogeneans namely Dactylogyrus in solitus and D. bopeleti gills parasites from Barbus martorelli reached their highest prevalence and their maximum intensity during the rainy seasons. Blahoua et al (2009) also observed that C. acerbus, C. halli and Scutogyrus minus appeared to be more prevalent and more abundant in long rainy season. Our results can be explained by water temperature which is assumed to be an important factor in controlling the occurrence of Monogeneans Simkova et al, 2001).…”
Section: Discussionmentioning
confidence: 67%
“…Blahoua et al (2009) mentioned the presence in Sarotherodon melanotheron, the genus Scutogyrus and several species of Cichlidogyrus. Ibrahim (2012) showed that eight Monogenean species colonized the gills of Tilapia zillii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative data on population dynamics of these parasites remain scarce (Bilong Bilong and Tombi, 2005;Nwani et al, 2008). In Côte d'Ivoire, there is almost no information about the dynamics of Monogeneans parasites, the only existing data are from Blahoua et al (2009). In this respect, the composition of Tilapia zillii parasites and their prevalence and mean intensity in Ayame I Lake are of great scientific and applied interest.…”
Section: Introductionmentioning
confidence: 99%